Relationship Between Family Environment and Discipline Study in the Equivalency Education Program - Rahmatul Syafitri; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by the low learning discipline of children in the equality program at PKBM Karang Putih II, Padang City, allegedly due to the influence of a poor family environment. The purpose of this study was to examine the relationship between family environment and learning discipline in the equality program at PKBM Karang Putih II, Padang City. This type of research is quantitative correlational. In this study, the population is all residents studying the equivalence program package A, B, and C in 2021, totaling 87 people. The sampling technique is cluster random sampling. Samples were taken as much as 30% from each study group, namely as many as 26 samples. The data collection technique used is a questionnaire, the data collection tool uses a questionnaire containing a list of statements. The data analysis technique uses percentages. The results showed that (1) the description of the family environment had been carried out well, (2) the description of learning discipline in the equality program at PKBM Karang Putih had been carried out quite well, (3) the relationship between the family environment and learning discipline was categorized as strong (significant). It can be seen from the majority of residents who learn to give frequent statements. Based on the results of the data obtained, it can be concluded that the relationship between the family environment and learning discipline in the equality program at PKBM Karang Putih II has been carried out well.